INTRODUCTION TO THE SPECIALITY - Mehmonova Mashhura (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annontatsion: Purpose of mastering the discipline: acquisition by future specialists of fundamental economic knowledge, formation of logic of economic thinking and economic culture, teaching them basic methods of cognition and analysis of economic processes, ability to make sound decisions about economic problems related to their future; the formation of students integrated system of knowledge about future profession accountants intelligence, acquiring skills to navigate the successive stages of obtaining financial education in classical university, learning the basic concepts and categories of accounting and analytical science and practices to wide use acquired knowledge for competitive education in the first bachelor level.